Evaluating the impact of land development on water quality of the largest lakes in Malaysia - Maizatul Aida, Mohd Redzuan (2018)
A study on the impact of logging and agricultural activity towards water quality in Bera Lake was carried out in February until May 2018. Three sampling stations were selected for this study: logging area, agricultural area, and jetty station. Thirteen water quality parameters were considered in this study during study periods. The parameters were then analyzed and measured based on standard method. The water quality parameter were classified according to Department of Environment Water Quality Index (DOE-WQI) and National Water Quality Standard (NWQS) for Malaysia. The Biochemical Oxygen Demand (BOD) was high at logging area (3.73) and low at jetty station (2.7). The dissolved oxygen (DO) was high at agricultural area (5.54) and low at logging area (4.11). The Total Suspended Solid (TSS) was high at agricutural area (10.5) and low at jetty station (6). The water quality of Bera Lake falls into class II according to DOE-WQI. Therefore, it is suitable for recreational uses but need conventional treatment for water supply. Agricultural activity, such as palm oil plantation at Felda Triang, and logging activities at Pos Iskandar near the lake did affected water quality in Bera Lake. If these situations continued, may have caused Bera Lake environmental degradation and may affect the aquatic life and hydrological characteristics of water system in long term deterioration.